The practice of social entrepreneurship: Theory and the Swedish experience - Yohanan Stryjan (Hochschule Wismar, Fachbereich Wirtschaft, 2005)
The notion of social entrepreneurship has gained increasing recognition in the last years, both as an increasingly visible mode of economic action, and as an important policy tool. The paper outlines a typology that departs from a Schumpeterian view of entrepreneurship, that centers on the creation of new combinations of resources, and focuses on the nature of actors engaging in the pursuit, and the nature of resources mobilized. The analysis is illustrated by case study material on social enterprises that operate on the boundaries of the Swedish Welfare State, and historical examples taken from co-operative enterprises. Social entrepreneurship may be mapped on such a typology as a category of entrepreneurship that primarily (a) is engaged in by collective actors, and (b) involves, in a central role in the undertaking's resource mix, socially embedded resources. Social entrepreneurship that involves (or centers on) a business activity is one important subcategory of the field. It necessarily spans the boundary between different rule regimes that define resources and their utilization (cf. Polanyi 1944/2001: 57). The core business activity would thus involve the tapping of socially embedded resources and their conversion into (market-) convertible resources. As importantly, to ensure the undertaking's (or enterprise's) survival over time, it would also be expected to contribute to the replenishment of such resources, reconverting market resources into social capital.
Keywords: L33; L31; H42; L14; 330; Gemeinwesenarbeit; Unternehmer; Unternehmensgründung; Sozialer Dienst; Wohlfahrtsorganisation; Theorie; Schweden